Linear high intensity area along the medial margin of the internal segment of the globus pallidus in Machado-Joseph disease patients - Yamada, S; Nishimiya, J; Nakajima, T; Taketazu, F (Journal of neurology, neurosurgery and psychiatry, 2005)
Our new finding on magnetic resonance imaging (MRI) of Machado-Joseph disease (MJD) patients indicates degeneration of the lenticular fasciculus (LF), a major outflow of the internal segment of the globus pallidus (GPi). We examined the clinical, radiological, and autopsy findings of one MJD patient and then retrospectively reviewed the MRI images of another 15 patients looking for a similar abnormal signal intensity. The significance of the clinicoradiological correlation of the MRI finding was confirmed by examining the MRI images of 130 control subjects. In the autopsy case, abnormal linear high intensity areas were observed along the bilateral medial margins of the internal segments of the GPi on T2 weighted, FLAIR, and proton density images, but not on T1 weighted images. Pathologically, this abnormal signal intensity was consistent with degeneration of the LF. The same finding was also observed in the other 15 patients. In two patients the finding was only unilaterally observed. No control subject showed this MRI finding. In MJD patients, abnormal linear high intensity areas indicating LF degeneration are usually observed along the medial margin of the GPi on T2 weighted, FLAIR, and proton density sequences. To our knowledge, this MRI finding has not previously been described.